-9x+7=4x+1

Simple and best practice solution for -9x+7=4x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9x+7=4x+1 equation:


Simplifying
-9x + 7 = 4x + 1

Reorder the terms:
7 + -9x = 4x + 1

Reorder the terms:
7 + -9x = 1 + 4x

Solving
7 + -9x = 1 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
7 + -9x + -4x = 1 + 4x + -4x

Combine like terms: -9x + -4x = -13x
7 + -13x = 1 + 4x + -4x

Combine like terms: 4x + -4x = 0
7 + -13x = 1 + 0
7 + -13x = 1

Add '-7' to each side of the equation.
7 + -7 + -13x = 1 + -7

Combine like terms: 7 + -7 = 0
0 + -13x = 1 + -7
-13x = 1 + -7

Combine like terms: 1 + -7 = -6
-13x = -6

Divide each side by '-13'.
x = 0.4615384615

Simplifying
x = 0.4615384615

See similar equations:

| 3(x+2)-6=24 | | 5+8x=3x+15 | | 50x^2+20x-16=0 | | 6+0.10x=.15x+8 | | 9x-6y=30 | | -(3x-5)-(2x-6)+1=-5(x-1)-(3x+2)+3 | | 8x(7-24)=32 | | 8x(7-24)= | | -2p+120=3p+20 | | 0.5+0.05x=9.8 | | (x-3)(x^2+3x+9)=98 | | 0.5+0.05x=9.6 | | 3x=x+45 | | -14579x-63903= | | 1363x-15942x= | | -35x+1398x= | | 15942x+63903= | | 3d*5e= | | -35x+1373-15995+63210= | | 3cd-2cd= | | 3y=6x+5 | | 2x(2x-3)-(3x-1)(x+1)=-6 | | 9-7-7x-3x=4 | | 5.5p+7=1.5p+35 | | 2X+5-5X=-6+90 | | (x+1)(x-3)=(x+2)(x+2) | | 9-2x-7-13x=5 | | 2x-2+13= | | d^2F=15 | | x^2+9x+448=0 | | (X+4)(X+7)=70 | | y+5=-.454(x+13) |

Equations solver categories